Assessing the Effect of Earnings per Share on Equity Prices at Commercial Banks in Nepal - Rajesh Gurung; Paritosh Subedi (Interdisciplinary Journal of Management and Social Sciences, 2024)
The study aimed to investigate the relationships between market price per share (MPS) and its determinants—earnings per share (EPS), dividends per share (DPS), book value per share (BVPS), price-to-earnings (P/E) ratio, and total assets (TA)—in commercial banks in Nepal. The methodology is employed the stepwise regression analysis, the study examined data from 16 out of 19 listed commercial banks on the NEPSE, covering cross-sectional period from 2007 to 2023, with 171 yearly observations. The analysis revealed that EPS is undoubtedly an important variable, in addition to BVPS and the P/E ratio, to explain the MPS of commercial banks. Conversely, DPS and TA were found to have no significant effects on MPS. The study findings have far-reaching implications for Nepal’s economic sector, including bank financial health, investor behavior, market efficiency, and overall economic growth. Banks may improve their performance and support to contribute to a stable and prosperous economy by emphasizing on important financial parameters.